2019
DOI: 10.32479/ijefi.7640
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tax, Foreign Ownership and Company Size on the Application of Transfer Pricing in Manufacturing Companies Listed on Idx During 2013-2017

Abstract: The objective of this research is to examine the effects of tax, foreign iownership, and firm size on the application of transferi pricing in the manufacturing companies listed on Indonesia Stock Exchange (IDX) during 2013-2017. This study is hypothesis-testing research by using purposive sampling method with a total of 110 samples of data. Secondary data in the form of financial statements with the year ended 31 December were obtained from the IDX. Logistic regression was used to test the hypotheses. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 4 publications
2
3
0
5
Order By: Relevance
“…Teori ini meyakini bahwa tidak ada kecocokan antara manajemen perusahaan (agen) dengan pemegang saham/pemilik perusahaan (principal) yang dapat diperoleh dari manajemen perusahaan mengenai informasi internal dan prospek perusahaan di masa depan dibandingkan pemegang saham atau perusahaan lain. Principal menginginkan pengembalian yang maksimum atas investasi mereka, sedangkan agent mengharapkan imbalan atas pekerjaan yang telah mereka lakukan dengan pemberian insentif yang sesuai (Yulia, et al, 2019).…”
Section: Tinjauan Literatur Dan Hipotesis Teori Keagenan (Agency Theory)unclassified
“…Teori ini meyakini bahwa tidak ada kecocokan antara manajemen perusahaan (agen) dengan pemegang saham/pemilik perusahaan (principal) yang dapat diperoleh dari manajemen perusahaan mengenai informasi internal dan prospek perusahaan di masa depan dibandingkan pemegang saham atau perusahaan lain. Principal menginginkan pengembalian yang maksimum atas investasi mereka, sedangkan agent mengharapkan imbalan atas pekerjaan yang telah mereka lakukan dengan pemberian insentif yang sesuai (Yulia, et al, 2019).…”
Section: Tinjauan Literatur Dan Hipotesis Teori Keagenan (Agency Theory)unclassified
“…International transactions' positive effect on transfer pricing by using foreign ownership has been proved (Pratama, 2020). In the meantime, a study by (Yulia et al, 2019) investigating the international ownership relationship produced the opposite outcome. Research by Nazihah et al (2019) has revealed a positive impact on the bonus mechanism's transfer pricing decisions, which contrasts to Susanti & Firmansyah's study (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Teori keagenan menyimpulkan bahwa principal hanya tertarik pada peningkatan keuntungan dan investasi. Sedangkan, agen hanya tertarik pada kompensasi finansial berupa imbalan kerja (Yulia, et al, 2019).…”
Section: Agency Theoryunclassified